Power generation from the Cu26Nb2Ge6S32-based single thermoelectric element with Au diffusion barrier. Issue 17 (12th April 2019) - Chetty, Raju; Kikuchi, Yuta; Bouyrie, Yohan; Jood, Priyanka; Yamamoto, Atsushi; Suekuni, Koichiro; Ohta, Michihiro
Abstract : A conversion efficiency of ∼3.3% has been successfully demonstrated in colusite (Cu26 Nb2 Ge6 S32 )-based single thermoelectric element with Au diffusion barrier. Abstract : In this study, we have developed a diffusion barrier for thermoelectric colusite Cu26 Nb2 Ge6 S32 and evaluated the conversion efficiency of the Cu26 Nb2 Ge6 S32 -based single thermoelectric element. This Cu26 Nb2 Ge6 S32 -based single element with metal diffusion barriers (Ti, Pt, Ni, and Au) was prepared through hot pressing. Microstructural investigations revealed microcrack formation at the interface between the Ti/Pt diffusion barriers and Cu26 Nb2 Ge6 S32 due to the mismatch of the coefficient of thermal expansion between them. Although no cracks were observed at the interface between the Cu26 Nb2 Ge6 S32 and Ni diffusion barriers, secondary phases of Ni–S, Ni–Ge, and Cu–S were formed around the interface. A good match in the coefficient of thermal expansion between Cu26 Nb2 Ge6 S32 and Au resulted in a crack-free interface. Moreover, no secondary phases were found around the Cu26 Nb2 Ge6 S32 and Au interface. Therefore, the Au diffusion barrier allows a reduced specific contact resistance of 4–5 × 10 −10 Ω m 2 . In the conversion efficiency evaluation, the radiative heat transfer was compensated by using silica glass as a reference. The maximum thermoelectric conversion efficiency ( η max ) of ∼3.3% was estimated at the hot-side temperature ( T h ) of 570 K and the cold-side temperature ( T c ) of 297 K for the Cu26 Nb2 Ge6 S32 -based single element with a Au diffusion barrier. Three-dimensional finite-element simulations for the Cu26 Nb2 Ge6 S32 -based single element predicted the η max of ∼4.5% at T h and T c of 570 K and 297 K, respectively. Therefore, there is further scope for improvement in the performance of the Cu26 Nb2 Ge6 S32 -based element.